Drug–drug interactions of cytostatics with regular medicines in lung cancer patients. (October 2017) - Rompelman, Florentine MV; Smit, Adrianus AJ; Franssen, Eric JF; Crul, Mirjam
Background: Lung cancer patients have a high risk for drug–drug interactions, as they use numerous types of concomitant medicines including antineoplastic agents, cancer treatment co-medication, and medicines aimed at several types of comorbidities. Objective: The primary objective of this study is to determine the incidence and the clinical relevance of the drug–drug interactions between antineoplastic agents and regular medication used by lung cancer patients. Secondary objectives are (i) to determine the effectiveness of the medication review by the hospital pharmacists concerned, (ii) to establish which patients are most at risk of drug–drug interactions and (iii) to determine whether physicians comply with advice given by hospital pharmacists. Setting: This prospective study was undertaken in a Dutch hospital pharmacy, at Onze Lieve Vrouwe Gasthuis (OLVG), Amsterdam. Methods: All lung cancer patients receiving one or more cytotoxic agents during the period 21 June 2010 till 2 December 2014 at OLVG were included. The medication list of the patients was obtained electronically from the community pharmacy and checked for interactions by a hospital pharmacist. Interactions that required intervention according to the national database were the only ones taken into account. Interventions were recorded in the patients' electronic charts. All medication reviews were cross-checked and analyzed by an independent pharmacist at the end of the study period. Main outcome measure: Prevalence and clinical relevance of drug–drug interactions between antineoplastic agents and other types of medication in lung cancer patients. Results: A total of 298 lung cancer patients were included in this study. In 53 patients (18%), a total of 73 interactions with potential clinical relevance were found. The most frequent interaction was between cytostatics and coumarins while the most relevant one was between cisplatin and furosemide. According to statistical analysis, gender as well as the number of drugs prescribed were significant predictors for drug–drug interactions. Eighty-four percent of the interactions were discovered by pharmacists during daily routine. In 92% of the cases, the pulmonary physicians complied with the advice of the pharmacist. Conclusion: Eighteen percent of lung cancer patients treated with cytotoxic therapy had one or more relevant drug–drug interactions. This study shows that medication surveillance by a hospital pharmacist is necessary to prevent possible negative drug–drug interactions. Further research should focus on the clinical outcome of the interactions as well as on interactions between cytostatics and alternative medicines and/or over-the-counter medicines.